IMPLEMENTING THE NEW SENIOR SECONDARY SCHOOL CURRICULUM FOR THE REALIZATION OF THE OBJECTIVE OF ENTREPRENUERSHIP EDUCATION IN ONDO STATE, NIGERIA - Festus Oluwole Alabi (European Scientific Journal, ESJ, 2014)
The study examines the implementation of the new senior secondary school curriculum for the realization of the objective of entrepreneurship education in Ondo State, Nigeria Today ,many grandaunts from Nigerian Secondary Schools are unemployed and cannot employ themselves. They are curiously idle because they lack the pre-requisite for job creation despite the secondary education received. Descriptive research design of survey type was used. Ondo State is made up of three Senatorial districts (North, South and central) with 304 Public Senior Secondary Schools and over 280 Government approved Private Secondary Schools (EMIS, 2014) The target population from which the sample was selected consisted of 18 public secondary schools and 18 private secondary schools from each of the 3 Senatorial District in Ondo State, Nigeria selected through a simple random sampling and stratified random sampling methods. One Principal and 5 teachers were randomly selected from each school after stratification into urban and rural areas with equal chances. A total number of 108 principals and 590 teachers were sampled as respondents. Data were collected through the use of a self-developed and validated questionnaire tagged 'Implementation of the New Senior Secondary Curriculum Descriptive Questionnaire' (INSSCDQ). with a reliability coefficient of r = 0.76. One research question and two hypotheses were generated and tested. The result shows that there is a significant difference in the Perception of Teachers in the implementation of New Senior Secondary School Curriculum between Public and Private senior secondary schools in Ondo State (t-cal=.667> t-val. = .564; P<.05). Also, the test performed showed that with means of 13619.10 for urban and 13323.33 for rural. Thus, the differences was not statistically significant (t-cal=.256< t-val. = .804; P>.05).The result provides a sufficient evidence to recommend that entrepreneurship education should be incorporated into secondary school programme right from the junior secondary. Also, Government and Proprietors of schools should ensure proper funding of schools to enable the provision of functional trade workshops and other facilities for effective teaching and learning of the trade subjects.